Shifting Private-Public Patterns in Short-Cycle Higher Education Across Europe - Slantcheva-Durst, Snejana (International Higher Education, 2015)
Short-cycle higher education is largely ignored by the literature, and yet it serves a growing number of students in Europe. This article discusses the realities and challenges of this aspect of higher education, focusing particularly on the private sector.